Negative effects of undernutrition on sputum smear conversion and treatment success among retreatment cases in Uganda: A quasi-experimental study - Izudi, Jonathan; Bajunirwe, Francis; Cattamanchi, Adithya (Elsevier Ltd, 2024)
The causal relationship between undernutrition and response to anti-tuberculosis (TB) treatment and TB treatment outcomes among people with retreatment TB is understudied. To evaluate the effect of undernutrition on treatment success and sputum smear conversion among people with retreatment drug-susceptible TB in Kampala, Uganda. We conducted a quasi-experimental study utilizing propensity score weighting among people with retreatment drug-susceptible TB aged ≥ 15 years treated between 2012 and 2022 in Kampala. The primary exposure was undernutrition assessed using the mid-upper arm circumference at the time of TB diagnosis. The primary outcome was treatment success defined as cure or treatment completion at month 6. Sputum smear conversion was the secondary outcome and was measured as a change in sputum smear status from positive to negative at months 2, 5, and 6. We estimated the causal effect of undernutrition on the outcomes using a propensity-score weighted modified Poisson regression model with robust error variance. Of the 605 participants, 432 (71.4 %) were male, 215 (35.5 %) were aged 25-34 years, 427 (70.6 %) had bacteriologically confirmed pulmonary TB, 133 (22.0 %) were undernourished and 398 (65.8 %) achieved treatment success. Of participants with bacteriologically confirmed pulmonary TB, 232 (59.0 %), 327 (59.3 %), and 360 (97.6 %) achieved sputum smear conversion at months 2, 5, and 6, respectively. Undernutrition reduced treatment success (RR 0.42, 95 % CI 0.32-0.55) as well as sputum smear conversion at months 2 (RR 0.45, 95 % CI 0.42-0.49) and 5 (RR 0.46, 95 % CI 0.43-0.51) but not month 6 (RR 0.99, 95 % CI 0.97-1.02). Undernutrition negatively impacts treatment outcomes. Therefore, nutritional assessment should be an integral component of TB care, with nutritional counseling and support offered to those undernourished to optimize their TB treatment response and outcomes.
Keywords: Malnutrition Propensity score analysis Sputum smear conversion Treatment success Tuberculosis and Undernutrition